PENGEMBANGAN SUMBERDAYA MANUSIA UMKM BERBASIS POTENSI LOKAL DI YOGYAKARTA - Suyatno; Dewi Amanatun Suryani (Yayasan Nusantara Hasana Berdikari, 2023)
The purpose of this study is to get the description of developing MSME human resources based on local potential in the Special Region of Yogyakarta, . This study uses a descriptive qualitative methodology; The object of this research is MSME’s Human Resources in the province of Yogyakarta. Primary data are obtained from observation and interviews with the informant; Secondary data is obtained from data from the Cooperatives, Small and Medium Enterprises Office, various media, articles, and homepages. The research was conducted in several stages: collecting data, editing, reducing data, and classification, then continued with data analyses and then make a conclusion narrative. Finding of the study is for developing MSME’s human resource, the government make program and policy, then collaborate with the related stakeholders to implement programs of training, coaching, counseling, and companioning based on their business. The Province Government develop more general skill and knowledge, while the Village and District Government develop specific skill based on the characteristics of the available local potential resources. Originality: The study focuses on the development of MSMEs’ Human Resources based on local potentials in Yogyakarta.